Emerging Creativity - Craig, Joshua Mark (East Carolina University, 2013)
Complex systems and patterns arise out of a multiplicity of relatively simple interactions. This phenomenon is defined as Emergence. Emergent systems can act as a guide to the creative process by allowing the artist to institute conditions under which unexpected interactions lead to creative insight.
Keywords: Fine arts; Art; Complexity theory; Creative process; Emergence; Metal-work; Jewelry making